Versatile cutting fracture evolution modeling for deformable object cutting simulation. (June 2022) - He, Sirui; Qian, Yinling; Zhu, Xin; Liao, Xiangyun; Heng, Pheng-Ann; Feng, Ziliang; Wang, Qiong
Highlights: Propose a versatile cutting fracture model based on Griffith's energy and introduce a tailored cut incision evolution scheme considering the interaction between the cutting tool and object. Propose a material-aware adaptation scheme for generating the indentation which is highly consistent with the cut tool blade and the visual plausible indentation-induced deformation. Conducte experiments on different models, materials, and tools with different shapes to prove the versatility of the proposed algorithm. Abstract: Background and Objectives: Soft body cutting simulation is the core module of virtual surgical training systems. By making full use of the powerful computing resources of modern computers, the existing methods have already met the needs of real-time interaction. However, there is still a lack of high realism. The main reason is that most current methods follows the "Intersection-IS-Fracture" mode, namely cutting fracture occurs as long as the cutting blade intersects with the object. To model real-life cutting phenomenon considering deformable objects' fracture resistance, this paper presents a highly realistic virtual cutting simulation algorithm by introducing an energy-based cutting fracture evolution model. Methods: We design the framework based on the co-rotational linear FEM model to support large deformations of soft objects and also adopt the composite finite element method (CFEM) to balance between simulation accuracy and efficiency. Then, a cutting plane constrained Griffth's energy minimization scheme is proposed to determine when and how to generate a new cut. Moreover, to provide the contact effect before the fracture occurs, we design a material-aware adaptation scheme that can guarantee indentation consistent with the cutting tool blade and visually plausible indentation-induced deformation to avoiding large computational effort. Results and conclusion: The experimental results demonstrate that the proposed algorithm is feasible for generating highly realistic cutting simulation results of different objects with various materials and geometrical characteristics while introducing a negligible computational cost. Besides, for different blade shapes, the proposed algorithm can produce highly consistent indentation and fracture. Qualitative evaluation and performance analysis indicate the versatility of the proposed algorithm.